Knee Sepsis after Suprapatellar Nailing of an Open Tibia Fracture: Treatment with Acute Deformity and External Fixation - Chelsea E. Minoughan; Adam P. Schumaier; Frank R. Avilucea (Case Reports in Orthopedics)
Case. A 31-year-old male was involved in a dirt bike accident and sustained an isolated type II open mid-distal tibia fracture. The patient underwent suprapatellar intramedullary nailing and subsequently developed knee sepsis. Conclusion. This patient was managed with irrigation and debridements of the knee, fracture site, and intramedullary canal. A resultant soft-tissue defect over the fracture site obviated primary closure. Creation of an acute deformity stabilized by a Taylor spatial frame allowed primary wound closure. After soft tissue healing occurred, the frame was used to correct the intentional deformity and maintain reduction until full healing occurred.